PELATIHAN MANDIRI MERDEKA BELAJAR PADA PLATFORM MERDEKA MENGAJAR - Sonny Rohimat (Universitas Sultan Ageng Tirtayasa, 2022)
The Merdeka Mengajar Platform was launched as a follow-up to the decision on guidelines for implementing the learning recovery curriculum after the Covid-19 pandemic, which was the result of an evaluation of the implementation of the previous curriculum which was deemed unable to overcome learning loss. This research is a description of self-training activities on the topic of Merdeka Belajar with the aim of providing an adequate description to teachers so that they are more interested in participating in self-training on the Merdeka Mengajar platform. This research was conducted qualitatively using a descriptive method through three stages of activities, namely preparation, self-training, and real action. The training is carried out using an application that is downloaded and installed on an android phone, as well as logging in using a belajar.id account. The training is carried out by completing five modules which consist of materials in the form of learning videos, comprehension exercises, reflective stories, and ending with a post test, then followed by real actions in the form of spreading an understanding of Merdeka Belajar in a combination online and offline. Based on the feedback, in general, participants gained a better understanding of the concept of Merdeka Belajar and began to plan follow-up activities for dissemination. The results of the dissemination are reported in a real action sheet on the Merdeka Mengajar platform.